Assessing Usability of Products in the Low Vision Field - Wing, Craig Jason Tam (My University, 2007)
This paper presents the implementation of usability engineering into a device to meet the requirements of a Visually Impaired Person (VIP). Users of such a device may suffer from conditions such as Macular Degeneration, Diabetes and HIV/AID’s related disorders. Since these disorders affect a person’s vision, the device enlarges the desired text to reduce the effects of loss of vision. Other functionality may include image manipulation and colour modification. A usability engineering framework is incorporated into the design as well as accommodating user requirements in the design process. Usability principles are implemented, hence meeting the aims of effectiveness, efficiency, learnability, satisfaction and context of use. The device is examined via heuristic evaluation and usability testing from specialists and end users, with comments, ratings and times recorded. Research indicates that this device successfully implements usability engineering techniques and provides a cost effective, highly functional device for the VIP.
Student Number : 9804058J - MSc dissertation - School of Information and Electrical Engineering - Faculty of Engineering and the Built Environment
Keywords: VIP; CAL; macular degeneration; AMD; usabilty engineering; usabilty testing; heuristic evaluation; Nielsen; evolutionary delivery